David Toop, Sinister Resonance: The Mediumship of the Listener (2010) - Graham, Stephen (Journal of the Society for Musicology in Ireland, 2011)
A review of David Toop, Sinister Resonance: The Mediumship of the Listener (London & New York: Continuum, 2010), ISBN 978-1-4411-4972-5.